Improved measurement results for the Avogadro constant using a 28Si-enriched crystal. (25th March 2015) - Azuma, Y; Barat, P; Bartl, G; Bettin, H; Borys, M; Busch, I; Cibik, L; D'Agostino, G; Fujii, K; Fujimoto, H; Hioki, A; Krumrey, M; et al.
Abstract: New results are reported from an ongoing international research effort to accurately determine the Avogadro constant by counting the atoms in an isotopically enriched silicon crystal. The surfaces of two 28 Si-enriched spheres were decontaminated and reworked in order to produce an outer surface without metal contamination and improved sphericity. New measurements were then made on these two reconditioned spheres using improved methods and apparatuses. When combined with other recently refined parameter measurements, the Avogadro constant derived from these new results has a value of N A = 6.022 140 76(12) × 10 23  mol −1 . The x-ray crystal density method has thus achieved the target relative standard uncertainty of 2.0  ×  10 −8 necessary for the realization of the definition of the new kilogram.